Use of Apple Pomace as Substrate for Production of Lactiplantibacillus plantarum Malolactic Starter Cultures - Cerdeira, Victoria (2021)
The by-products of the food industry are an economic alternative as a source of nutrients to obtain biomass. At the same time, theiruse could solve the environmental problem related to their disposal, which is highly polluting due to their elevated biochemical oxygen demand. In this work, we seek to optimize the production of cellular biomass of two native Patagonian strains of Lactiplantibacillus plantarum (UNQLp 11 and UNQLp155), selected for its oenological and technological properties, using apple pomace (AP), a residue from the juice and cider industry. The supplementation of AP with yeast extract, salts, and Tween 80 (sAP), proved to maintain the growth of the Lpb. plantarum strains, similar to the commercial medium used to grow LAB (De Man, Rogosa, Sharpe, MRS). Cultures grown in sAP medium showed good tolerance to wine conditions (high ethanol content and low pH), demonstrated by its ability to consume L-malic acid. The subsequent inoculation of these cultures in sterile wines (Merlot and Pinot noir) was carried out at laboratory scale, evaluating cell viability and L-malic acid consumption for 21 days at 21◦C. Cultures grown in sAP media showed a similar performance to MRS media. Thus, sAP media proved to be a suitable substrate to grow oenological Lpb. plantarum strains where cultures (with high size inoculums) were able to drive malolactic fermentation, with an L-malic acid consumption higher than 90%.